Impact of Disconnected Pancreatic Duct Syndrome on the Endoscopic Management of Pancreatic Fluid Collections. Issue 3 (March 2018) - Bang, Ji Young; Wilcox, Charles Melbern; Navaneethan, Udayakumar; Hasan, Muhammad K.; Peter, Shajan; Christein, John; Hawes, Robert; Varadarajulu, Shyam
Abstract : Objective: To study the effect of disconnected pancreatic duct syndrome (DPDS) on endoscopic management of pancreatic fluid collections (PFCs). Background: Data on the impact of DPDS in patients undergoing endoscopic treatment of PFCs are limited. Methods: Retrospective study of patients undergoing endoscopic drainage of PFCs from 2003 to 2015. If treatment response was suboptimal following initial endoscopic or endoscopic ultrasound–guided transmural drainage, hybrid interventions (endoscopic ultrasound–guided multigate/dual modality technique, endoscopic/percutaneous sinus tract necrosectomy) were performed. Transmural stents were left permanently in situ in DPDS patients from 2008 onwards. Main outcome measures were to evaluate the effect of DPDS on need for hybrid treatment, reinterventions, rescue surgery, length of stay, and overall treatment success. Results: Of 361 patients, 34 (9.4%) were acute collections, 178 (49.3%) pseudocysts, and 149 (41.3%) walled-off necrosis (WON). DPDS was present in 167 (46.3%) patients, absent in 124 (34.3%), unknown in 70 (19.4%), and occurred more frequently in WON compared to other PFCs (68.3% vs 31.7%; P < 0.001). Although there was no difference in treatment success, more patients with DPDS required hybrid treatment (31.1% vs 4.8%, P < 0.001), reinterventions (30% vs 18.5%, P = 0.03), rescue-surgery (13.2% vs 4.8%, P = 0.02), and longer length of stay [median (interquartile range) days, 3 (2–10) vs 2 (1–4), P = 0.003]. PFC recurrence was lower in patients with DPDS with permanent transmural stents (17.4% vs 1.7%, P < 0.001). On multivariate logistic regression, DPDS [odds ratio (OR) 2.99], WON (OR 3.37), PFC size of 100 mm or more (OR 2.66), and multiple PFCs (OR 10.6) were associated with need for hybrid treatment. Conclusions: DPDS has a significant effect on endoscopic management of PFCs as more patients required hybrid treatment, reinterventions, and rescue surgery for achieving optimal clinical outcomes. Abstract : Supplemental Digital Content is available in the text